2006
DOI: 10.1017/s0950268806007679
|View full text |Cite
|
Sign up to set email alerts
|

Emerging epidemic diseases of frogs in Britain are dependent on the source of ranavirus agent and the route of exposure

Abstract: A series of transmission studies was conducted to investigate the aetiology, or aetiologies, of emerging fatal epidemic disease syndromes affecting the common frog (Rana temporaria) in Britain. The syndromes, characterized by skin ulceration or systemic haemorrhages, were induced upon exposure to lesion homogenates or cultured ranavirus. The re-isolation of ranavirus from experimentally affected frogs fulfilled Koch's postulates. Aeromonas hydrophila, previously associated with similar lesions, was not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 31 publications
2
83
0
Order By: Relevance
“…Ranaviruses can be transmitted by contact with infected individuals, through the water or on fomites (e.g., pond substrates), and by consuming part or all of infected animals (Langdon et al 1988 ;Reddacliff and Whittington 1996 ;Jancovich et al 1997 ;Plumb and Zilberg 1999b ;Woodland et al 2002b ;Pearman et al 2004 ;Harp and Petranka 2006 ;Brunner et al 2007 ;Cunningham et al 2007a ;Robert et al 2011 ;Brenes et al 2014a ). Viral mRNA is detectable in the intestines of larval and adult African clawed frogs ( Xenopus laevis ) as early as 3 h after exposure to virus in water and then spreads to other tissues, suggesting that the intestines are a primary point of entry of waterborne virus in amphibians (Robert et al 2011 ).…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%
“…Ranaviruses can be transmitted by contact with infected individuals, through the water or on fomites (e.g., pond substrates), and by consuming part or all of infected animals (Langdon et al 1988 ;Reddacliff and Whittington 1996 ;Jancovich et al 1997 ;Plumb and Zilberg 1999b ;Woodland et al 2002b ;Pearman et al 2004 ;Harp and Petranka 2006 ;Brunner et al 2007 ;Cunningham et al 2007a ;Robert et al 2011 ;Brenes et al 2014a ). Viral mRNA is detectable in the intestines of larval and adult African clawed frogs ( Xenopus laevis ) as early as 3 h after exposure to virus in water and then spreads to other tissues, suggesting that the intestines are a primary point of entry of waterborne virus in amphibians (Robert et al 2011 ).…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%
“…In amphibians, outbreaks of ranaviral disease are most often observed in larvae and recently metamorphosed animals (Green et al 2002 ;Docherty et al 2003 ;Balseiro et al 2009Balseiro et al , 2010; however, outbreaks that include adult animals are increasingly recognized (Cunningham et al 2007 ;Cheng et al 2014 ). Moreover, Earl and Gray ( 2014 ) demonstrated that ranavirus-associated mortality of larvae or metamorphs was suffi cient to cause population declines in highly susceptible species.…”
Section: Field and Clinical Findingsmentioning
confidence: 99%
“…Alternatively, infection could be maintained in adult frogs that experience infection but do not always succumb to disease. In support of this proposal, it has been observed that breeding common frogs presenting the systemic haemorrhagic form of ranavirosis often present healed skin ulcers that indicate a bout of disease the preceding year (Cunningham et al 2007b). …”
Section: Discussionmentioning
confidence: 91%
“…Signs of disease exhibited by toads did not include the superficial skin lesions that have been reported in larvae of North American amphibians dying from ranavirosis (Greer et al 2005, Duffus et al 2008) and the skin and abdominal haemorrhages that were typically presented by infected R. temporaria tadpoles. Haemorrhages are a source of infectious ranavirus that can be transmitted both directly and indirectly to susceptible hosts (Pearman et al 2004, Cunningham et al 2007b. Because toads do not present these signs of disease, they are less likely to be a significant source of infectious v www.esajournals.org ranavirus and rare infections in UK common toads appear most likely to have arisen through spill-over from diseased R. temporaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation